Papillotomy: indications - Delgado Pereira, Bolívar (Cirugía del Uruguay, 2020)
A survey is carried out of papillotomy on the basis of 63 cases treated throughout the last 10 years. A correct operative indication is the basis of satisfactory longterm results. Inflammatory papillary stenosis is the most common causative factor, frequently wet with in connection with repeated bilé-duct surgery and associated with common duct lithiasis, followed by gallstone impactation in the ampoule ( tactical indication) and, far less frequently, by chronic pancreatitis, Wirsung's exploration and oddian hypertony.